Occupational opportunities among the Alumni of a Nursing Institution in Western India - Kumari , Poonam; Kaushik, Narendra; Kumari , Chotu (American Journal of Biomedicine and Pharmacy, 2026)
Introduction: Professional performance of the alumni is one of the quality indicators of educational institutions. Nursing education institutions can use their alumni's performance analysis results to enhance their curricula, eliminate deficiencies, and improve the quality of education and graduate more highly qualified nurses. The present study was planned to evaluate the view of alumni of Govt. college of Nursing, Bikaner regarding nursing profession in term of appointment/placement and job satisfaction. Methodology: A descriptive cross sectional research design was used to find out the occupational opportunities of alumni of Government College of nursing Bikaner. Non-probability Convenient Sampling Technique was used to select 206 alumni. The data collection was done by structured job satisfaction and job placement checklists. Results: In terms of professional qualifications among alumni, 139 were master of Nursing while 67 were bachelor of nursing. In terms of mode of recruitment of job, the findings highlighted that out of 152 alumni were selected by competition while 21 have selected by interview. Conclusion: The present study concluded that out of 206 alumni, 89.32% were having job. The majority of alumni have good job appointment. The present study enhances the outcomes of institution in terms of occupational opportunities.